The Role of Artificial Intelligence and Big Data in the Transformation of Recruitment Processes and Financial Analysis: A Systematic Literature Review - Masno Marjohan; Wahyu Hidayat; Adi Pratama; Beta Mentari; Amelia Putri; Endah Sri Rahayu; Azian M Safan (Lafadz Jaya Publisher, 2025)
This study aims to explore the transformative role of Artificial Intelligence (AI) and Big Data in recruitment processes and financial analysis. Through a systematic literature review approach, data were collected from national journals published in the last five years. The findings show that AI has significantly improved the efficiency and objectivity of candidate selection by automated screening based on skill-matching algorithms. Meanwhile, Big Data analytics enhances financial decision-making by enabling real-time insights into company performance, profitability, and risk. The integration of these technologies not only optimizes human resources and financial management but also demands robust data governance This research concludes that successful implementation of AI and Big Data must be holistic combining technical, managerial, perspectives to build adaptive, accurate, and sustainable organizational systems.